Efektivitas Penerimaan Negara Bukan Pajak di Kantor Polisi Sektor Jatinangor Resor Sumedang - Whita Kaustavia; Ai Siti Farida (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2021)
This research is motivated by frequent errors in the production process of Police Notes which are included in the Non-Tax State Revenue which is managed by the Jatinangor Sector Police, Sumedang Resort, which causes the blank material to be damaged. The purpose of this study was to determine how the effectiveness of non-tax state revenue at the Jatinangor Police Sector, Sumedang Resort. This research refers to the theory of oganization effectiveness according to Mott (1972), that organizational effectiveness is influenced by three dimensions, namely, productivity, flexibility and adaptability. The research method used is descriptive method with a qualitative approach. Data collection techniques, using observation, interviews, study documentation, and triangulation. The data analysis technique used the Miles and Hubberman model with the stages of reduction, data presentation, and conclusion drawing. The results showed that the effectiveness of Non-Tax State Revenues in the Jatinangor Sector Police Station, Sumedang Resort, was running effectively. This is based on the dimensions of productivity, flexibility and adaptability that have gone well.